2016
DOI: 10.1530/erc-16-0147
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential response predictors to capecitabine/temozolomide in metastatic pancreatic neuroendocrine tumors

Abstract: The capecitabine and temozolomide (CAPTEM) regimen is active in the treatment of metastatic pancreatic neuroendocrine tumors (pNETs), with response rates ranging from 30 to 70%. Small retrospective studies suggest that O 6 -methylguanine DNA methyltransferase (MGMT) deficiency predicts response to temozolomide. High tumor proliferative activity is also commonly perceived as a significant predictor of response to cytotoxic chemotherapy. It is unclear whether chromosomal instability (CIN), which correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 21 publications
5
116
1
6
Order By: Relevance
“…A Spanish multicenter study and the single-center experience of Cives et al [30] revealed very similar results in terms of response and outcome [31]. Response rates were 47.7 and 54% with additional disease stabilization rates of 41.5 and 35% respectively.…”
Section: Recently Published Studies Confirming the Role Of Chemotheramentioning
confidence: 88%
See 2 more Smart Citations
“…A Spanish multicenter study and the single-center experience of Cives et al [30] revealed very similar results in terms of response and outcome [31]. Response rates were 47.7 and 54% with additional disease stabilization rates of 41.5 and 35% respectively.…”
Section: Recently Published Studies Confirming the Role Of Chemotheramentioning
confidence: 88%
“…TEM monotherapy has a long tradition in glioblastoma and melanoma, though in PNETs it was described to have only marginal benefits [26]. Therefore, combination regimens were evaluated revealing impressive objective response rates (RR) and good tolerability for the TEM-CAP combination therapy [27,28,29,30,31]. However, due to the limited availability of data and prospective clinical trials, the current guidelines recommend the TEM-CAP combination only as an alternative but not superior treatment to STZ/5-FU.…”
Section: Current Standard Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As this combination is used widely in mCRC, the same safety considerations apply. A commonly applied systemic approach to metastatic NETs is an oral combination regimen of capecitabine and temozolomide (CapTem), which alone has a 60% objective response rate for well-differentiated NETs (119). A feasibility and safety study of integrated CapTem and SIRT delivered on day 7 of the 14-day cycle, demonstrated no worse than additive toxicities, with better than expected disease control in the liver, suggesting a synergy justifying expansion into a phase II trial (120).…”
Section: Netsmentioning
confidence: 99%
“…50% of cases) [229][230][231]. However, determination of MGMT expression or methylation state is not currently recommended as a criterion for the use of chemotherapy.…”
Section: Szkolenie Podyplomowementioning
confidence: 99%